Analisis Kebijakan Izin Tinggal Permanen kepada Pencari Suaka Suriah di Swedia tahun 2013-2014 - Ambarani, Rizki Nadhilah; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
The Syrian conflict that started from 2011 brings down civil casualties and creates the biggest refugee crisis in the world. Since then many Syrians are trying to go outside the border of their country to find and get protection from other countries. European countries become one of the most popular destination for the refugees and asylum seekers. Sweden get the most Syrian asylum applicant per capita in 2012. Sweden that governed by Alliance regime in 2013, decides to make a policy to give permanent residence permit for all of Syrian asylum seeker that come to their country. This research used qualitative methods alongside with ignoring and compromise approach in Foreign Policy Analysis theory to explain reason behind Sweden’s government decision to give permanent residence permit for Syrian asylum seeker in 2013. The result of this research indicated that the policy regarding permanent residence permit for Syrian asylum seeker were government’s strategies ( ignoring and compromise) for the existence of populist party Sweden Democrats for the first time in Sweden’s parliament after winning 2010 elections.